La représentation médiatique du don et de la transplantation d’organes dans la presse suisse romande - Raphaël Hammer (Communication)
A content analysis of Swiss French-speaking newspapers reveals their representation of organ donation and transplantation. A largely uncritical and unchallenged discourse of legitimization based on a portrayal of the patient and on the argument of an organ shortage characterizes this representation. Far from debating the issue, newspaper articles establish a consensus around organ donation as a medical procedure, as a moral gesture and as a social institution.